Evaluation of Brain Natriuretic Peptide as a Predictor of Contrast Induced Acute Kidney Injury Post Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome - Abdelraouf, Islam Mohamed; Badr, Seham Fahmy; Ibrahim, IbtsamKhairat; Elsokkary, Hatem Mohamed (International Journal of Innovative Research in Medical Science, 2023)
Background: Brain (b-type) natriuretic peptide (BNP) is released into the circulation in response to ventricular dilatation and pressure overload conditions. Studies linked between levels of BNP and short/long term prognosis in patients of acute coronary syndrome (ACS). Aim: To evaluate the brain natriuretic peptide as a predictor of contrast induced acute kidney injury post percutaneous coronary intervention in patients with acute coronary syndrome. Patients and Methods: The study included 60 patients who presented to emergency room with diagnosis of ACS syndrome (ST segment elevation myocardial infarction (STEMI), non-ST segment elevation MI (NSTEMI) or unstable angina (UA)) who underwent to percutaneous coronary intervention. All participants subjected to history taking, clinical assessment, ECG, echocardiography and laboratory investigation (serum level of Troponin I, creatinine, blood urea and BNP). Results: Considering BNP levels at admission, CIN group has significantly elevated BNP level than non-CIN group (p<0.001). Value of BNP >69.0 pg/mL can strongly discriminate patients with CIN as AUC was 0.861 and p-value was <0.001 with sensitivity and specificity was81.8% & 92.6% respectively. Conclusion: BNP with cutoff value >69.0 pg/mL is a simple and easily measurable biomarker that can predict CIN in patients with acute myocardial infarction.